Pendampingan Progam Penyusunan Artikel Ilmiah bagi Siswa MA Unggulan K.H. Abd. Wahab Hasbulloh Bahrul Ulum Tambakberas Jombang melalui Strategi Service-Learning - Arif, Miftakhul (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
The writing ability of Indonesian students is generally low. It was marked by the lack of young writers in Indonesia who are able to produce scientific papers. Madrasah Aliyah Featured K.H. Abd. Wahab Hasbulloh (MAUWH) Bahrul Ulum Tambakberas Jombang is one of the boarding school-based formal education institutions that are committed to printing students to have the ability to write scientific articles. With a service-learning approach, community mentoring activities in MAUWH aims to (1) develop a program of writing scientific articles in the assisted community environment; and (2) improving the ability of assisted participants in preparing scientific articles. This community assistance activity is carried out through three stages, namely pre-implementation, implementation and post-implementation. Through the involvement of internal and external stakeholders, this community assistance activity succeeded in developing a scientific article writing program at MAUWH. It was marked by the drafting of the guidebook for writing scientific articles, the publication of the Journal El-Hijaz with the OJS (Open Journal System) System, and the output of scientific research in the form of journal articles.